The MBA Handbook : Academic and Professional Skills for Mastering Management - Cameron, Sheila (Pearson International Content, 2020)
Put ideas into practice using theoretical concepts and real-life examples The MBA Handbook, 9th Edition, by Cameron is a vital resource for MBA and other postgraduate management students to gain maximum learning benefit from their programme. This clearly structured handbook addresses the specific challenges of management study and the transferable skills required to meet these, including: <ul class="BulletListStyle1 SCXW133772797 BCX0" role="list" style="margin: 0px; padding: 0px; user-select: text; -webkit-user-drag: none; -webkit-tap-highlight-color: transparent; overflow: visible; cursor: text; font-family: verdana;"><li aria-setsize="-1" class="OutlineElement Ltr BCX0 SCXW133772797" data-aria-level="1" data-aria-posinset="1" data-font="Symbol" data-leveltext="" data-listid="11" role="listitem" style="margin: 0px 0px 0px 24px; padding: 0px; user-select: text; -webkit-user-drag: none; -webkit-tap-highlight-color: transparent; overflow: visible; cursor: text; clear: both; position: relative; direction: ltr; display: block; font-size: 10pt; font-family: Calibri, Calibri_MSFontService, sans-serif; vertical-align: baseline;"> Managing self, time, stress and the risks associated with study <li aria-setsize="-1" class="OutlineElement Ltr BCX0 SCXW133772797" data-aria-level="1" data-aria-posinset="2" data-font="Symbol" data-leveltext="" data-listid="11" role="listitem" style="margin: 0px 0px 0px 24px; padding: 0px; user-select: text; -webkit-user-drag: none; -webkit-tap-highlight-color: transparent; overflow: visible; cursor: text; clear: both; position: relative; direction: ltr; display: block; font-size: 10pt; font-family: Calibri, Calibri_MSFontService, sans-serif; vertical-align: baseline;"> Learning and professional development, including reflective and action learning, critical reading and thinking and using data and other evidence <li aria-setsize="-1" class="OutlineElement Ltr BCX0 SCXW133772797" data-aria-level="1" data-aria-posinset="3" data-font="Symbol" data-leveltext="" data-listid="11" role="listitem" style="margin: 0px 0px 0px 24px; padding: 0px; user-select: text; -webkit-user-drag: none; -webkit-tap-highlight-color: transparent; overflow: visible; cursor: text; clear: both; position: relative; direction: ltr; display: block; font-size: 10pt; font-family: Calibri, Calibri_MSFontService, sans-serif; vertical-align: baseline;"> Working with others, including teamwork and leadership, group creativity and problem solving <li aria-setsize="-1" class="OutlineElement Ltr BCX0 SCXW133772797" data-aria-level="1" data-aria-posinset="4" data-font="Symbol" data-leveltext="" data-listid="11" role="listitem" style="margin: 0px 0px 0px 24px; padding: 0px; user-select: text; -webkit-user-drag: none; -webkit-tap-highlight-color: transparent; overflow: visible; cursor: text; clear: both; position: relative; direction: ltr; display: block; font-size: 10pt; font-family: Calibri, Calibri_MSFontService, sans-serif; vertical-align: baseline;"> Demonstrating learning, including academic writing for assignments and exams, making presentations, building portfolio, and assessment for and during employment <li aria-setsize="-1" class="OutlineElement Ltr BCX0 SCXW133772797" data-aria-level="1" data-aria-posinset="5" data-font="Symbol" data-leveltext="" data-listid="11" role="listitem" style="margin: 0px 0px 0px 24px; padding: 0px; user-select: text; -webkit-user-drag: none; -webkit-tap-highlight-color: transparent; overflow: visible; cursor: text; clear: both; position: relative; direction: ltr; display: block; font-size: 10pt; font-family: Calibri, Calibri_MSFontService, sans-serif; vertical-align: baseline;"> Consultancy, research and project management With real-life case studies, business examples, new activities and exercises in every chapter, this successful text is designed to prepare and support students early in their studies, at key points during the programme, and well into their subsequent career. It also aid